Mortality and Health Outcomes in HIV-Infected and HIV-Uninfected Mothers at 18–20 Months Postpartum in Zomba District, Malawi - Landes, Megan (Public Library of Science, 2012)
BACKGROUND: Maternal morbidity and mortality among HIV-infected women is a global concern. This study compared mortality and health outcomes of HIV-infected and HIV-uninfected mothers at 18–20 months postpartum within routine prevention of mother-to-child transmission of HIV (PMTCT) services in a rural district in Malawi. METHODS: A retrospective cohort study of mother-child dyads at 18–20 months postpartum in Zomba District. Data on socio-demographic characteristics, service uptake, maternal health outcomes and biometric parameters were collected. RESULTS: 173 HIV-infected and 214 HIV-uninfected mothers were included. HIV-specific cohort mortality at 18–20 months postpartum was 42.4 deaths/1000 person-years; no deaths occurred among HIV-uninfected women. Median time to death was 11 months post-partum (range 3–19). Women ranked their health on a comparative qualitative scale; HIV-infected women perceived their health to be poorer than did HIV-uninfected women (RR 2.4; 95% CI 1.6–3.7). Perceived maternal health status was well correlated with an objective measure of functional status (Karnofsky scale; p<0.001). HIV-infected women were more likely to report minor (RR 3.8; 95% CI 2.3–6.4) and major (RR 6.2; 95% CI 2.2–17.7) signs or symptoms of disease. In multivariable analysis, HIV-infected women remained twice as likely to report poorer health [adjusted OR (aOR) 2.3; 95% CI 1.4–3.6], as did women with low BMI (aOR 2.1; 95% CI 1.1–4.0) and scoring lowest on the welfare scale (aOR 2.0; 95% CI 1.1–3.8). CONCLUSIONS: HIV-infected women show increased mortality and morbidity at 18–20 months postpartum. In our rural Malawian operational setting, where there is documented under-application of ART and poor adherence to PMTCT services, these results support attention to optimizing maternal participation in PMTCT programs.